Care for critically and terminally ill patients and moral distress of physicians and nurses in tertiary hospitals in South Korea: A qualitative study. - Jiyeon Kang; Eun Kyung Choi; Minjeong Seo; Grace S Ahn; Hye Youn Park; Jinui Hong; Min Sun Kim; Bhumsuk Keam; Hye Yoon Park (PLoS ONE)
Physicians and nurses working in acute care settings, such as tertiary hospitals, are involved in various stages of critical and terminal care, ranging from diagnosis of life-threatening diseases to care for the dying. It is well known that critical and terminal care causes moral distress to healthcare professionals. This study aimed to explore moral distress in critical and terminal care in acute hospital settings by analyzing the experiences of physicians and nurses from various departments. Semi-structured in-depth interviews were conducted in two tertiary hospitals in South Korea. The collected data were analyzed using grounded theory. A total of 22 physicians and nurses who had experienced moral difficulties regarding critical and terminal care were recruited via purposive maximum variation sampling, and 21 reported moral distress. The following points were what participants believed to be right for the patients: minimizing meaningless interventions during the terminal stage, letting patients know of their poor prognosis, saving lives, offering palliative care, and providing care with compassion. However, family dominance, hierarchy, the clinical culture of avoiding the discussion of death, lack of support for the surviving patients, and intensive workload challenged what the participants were pursuing and frustrated them. As a result, the participants experienced stress, lack of enthusiasm, guilt, depression, and skepticism. This study revealed that healthcare professionals working in tertiary hospitals in South Korea experienced moral distress when taking care of critically and terminally ill patients, in similar ways to the medical staff working in other settings. On the other hand, the present study uniquely identified that the aspects of saving lives and the necessity of palliative care were reported as those valued by healthcare professionals. This study contributes to the literature by adding data collected from two tertiary hospitals in South Korea.